The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/0017896910364831
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of assessing alcohol use among college students using wireless mobile devices: Implications for health education and behavioural research

Abstract: Objective: This study examined the feasibility of using wireless mobile devices (MDs) to collect daily alcohol information among college students, in particular examining feasibility in the context of costs associated with the use of wireless MDs. This study reports on practical aspects of using MDs to collect alcohol data, including compliance, technical success, user preferences for completing MD-based assessments, and cost. Setting: The study took place at a large, public university in the south-eastern Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…34 For instance, some studies have found that realtime feedback of users' health status and motivational messages via social media platforms and mobile devices can have a positive impact on controlling behaviors such as alcohol consumption, exercise, diet, and sexual behavior. 35,36 In our study, most physicians agree that ICTs can be useful in the promotion of health and medical services (87.4% and 84.3%, respectively). As eHealth applications continue to grow, they will allow for more personalized patient care, guiding patients when choosing a health professional, while providing relevant health information in the process.…”
Section: Discussionmentioning
confidence: 50%
“…34 For instance, some studies have found that realtime feedback of users' health status and motivational messages via social media platforms and mobile devices can have a positive impact on controlling behaviors such as alcohol consumption, exercise, diet, and sexual behavior. 35,36 In our study, most physicians agree that ICTs can be useful in the promotion of health and medical services (87.4% and 84.3%, respectively). As eHealth applications continue to grow, they will allow for more personalized patient care, guiding patients when choosing a health professional, while providing relevant health information in the process.…”
Section: Discussionmentioning
confidence: 50%
“…EMA offers methodological advantages to recall-based tools, including real-time reporting of mood, behavior, and environment (Forbes et al, 2012;Armey et al, 2011;Shrier et al, 2012;Wenze & Miller, 2010). EMA data are collected via cellular phone but historically collection involved sending automated surveys via handheld devices such as palm pilots (Collins, Kashdan, & Gollnisch, 2003;Shrier, Shih, Hacker, & de Moor, 2007). Adolescent cell phone ownership rates increase each year.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Health promoters have described the use of 'real-time feedback' of users' health status and 'prompts' and 'motivation' messages to 'change unhealthy lifestyle habits' via social media platforms and mobile devices, with reference to controlling behaviours such as smoking, alcohol consumption, exercise, diet and sexual behaviour (Mays et al, 2010;Laakso et al, 2011). One study, for example, reported the use of mobile devices to collect daily information about alcohol consumption among a group of American college students, referring to the devices' ability to administer 'just-intime' interventions to intercept unhealthy behaviours as they happen in real time (Mays et al, 2010). Such researchers frequently make reference to linking healthpreventive strategies using m-health devices with 'acceptance of greater personal consumer responsibility for healthy lifestyles', as Mays et al (2010, p. 311) …”
Section: Introductionmentioning
confidence: 99%